1998
DOI: 10.1051/rnd:19980110
|View full text |Cite
|
Sign up to set email alerts
|

Non-isotopic detection of nucleolar transcription in pre-implantation mouse embryos

Abstract: -Nucleolar transcription was analysed in permeabilized pre-implantation mouse embryos at the four-cell, eight-cell, morula and early blastocyst stages using confocal microscopy to detect incorporated 5-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…By statistical analysis of more than 100 embryos microinjected with BrUTP/␣-amanitin, we could show that nascent pre-rRNAs are first observed at the middle-end of the second cell cycle, around 44 -45 hphCG, and simultaneously in the 2 blastomeres. Transcription sites are associated with the surface of NPBs, in agreement with previous data (Koberna et al, 1998), and we showed here for the first time that they are also associated with small UBF/pol I (RPA116) foci, which decorate the NPBs as necklace-like structures, and thus represent ribosomal gene-bound transcription complexes. Furthermore, the major transcription factors are actually assembled at their rDNA targets at 40 hphCG, i.e., 4 -5 h before the onset of rDNA transcription.…”
Section: Discussionsupporting
confidence: 92%
“…By statistical analysis of more than 100 embryos microinjected with BrUTP/␣-amanitin, we could show that nascent pre-rRNAs are first observed at the middle-end of the second cell cycle, around 44 -45 hphCG, and simultaneously in the 2 blastomeres. Transcription sites are associated with the surface of NPBs, in agreement with previous data (Koberna et al, 1998), and we showed here for the first time that they are also associated with small UBF/pol I (RPA116) foci, which decorate the NPBs as necklace-like structures, and thus represent ribosomal gene-bound transcription complexes. Furthermore, the major transcription factors are actually assembled at their rDNA targets at 40 hphCG, i.e., 4 -5 h before the onset of rDNA transcription.…”
Section: Discussionsupporting
confidence: 92%